Adhesive contact of a rigid circular cylinder to a soft elastic substrate – the role of surface tension1. Issue 19 (21st May 2015) - Liu, Tianshu; Jagota, Anand; Hui, Chung-Yuen
<x xml:space="preserve">Abstract</x> This article studies the effects of surface tension on the adhesive contact mechanics of a long rigid cylinder on an infinite half space comprising an incompressible elastic material.